Innovation in Fiction Text Learning Models Based on Humanistic Values For Strengthening Literacy Critical Learners - Mulyadin Mulyadin; Ni Made Dainivitri Sinta Sari; Ni Wayan Eka Widiastini; Muhammad Hafidzin; I Nyoman Sudiana; Ida Bagus Putrayasa (Prodi PAI STIT Sunan Giri Bima, 2025)
Study This aim developing learning models text fiction of a nature transformative , so that No only focus on understanding literary elements , but also in the formation of character , empathy , and ability think reflective participant educate . Approach This based on need will participatory , contextual , and adaptive learning to development modern education . Research use method model development with stages analysis needs , formulation objectives , preparation syntax , development teaching materials , trials , reflection , and dissemination . Approach interdisciplinary and digital media utilization is applied For enrich experience Study as well as grow creativity and collaboration participant education . Research results show that learning model text developed fiction​ own characteristics contextual , integrative , creative , collaborative , and reflective . This model push involvement active participant educate in reading and appreciating text fiction as representation reality social and cultural . The application of proven models increase literacy participant educate in a way holistic , encompassing ability reading , writing , listening , and speaking . In addition , the values character like empathy , responsibility responsibility and tolerance develop through meaning to conflict and moral message in text fiction . Research This conclude that learning model text innovative and humanistic fiction​ effective strengthen quality learning Indonesian and​ contribute to the formation of culture literacy in the modern era.